1983
DOI: 10.1177/000348948309200110
|View full text |Cite
|
Sign up to set email alerts
|

Immune Complexes in Middle Ear Fluid in Chronic Secretory Otitis Media

Abstract: Data on 87 patients (113 ears) with chronic secretory otitis media (SOM) are reported. The bacteriological analysis of the middle ear fluid (MEF) revealed Streptococcus pneumoniae in 7% of ears, Hemophilus influenzae in 9%, opportunistic bacteria in 20%, while 64% of the samples showed no growth. Free capsular polysaccharide pneumococcal antigens were found in 5% of the MEF samples using counterimmunoelectrophoresis (CIEP) with Omniserum containing 83 different pneumococcal polysaccharide types. Heating of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…It has been reported that serous and mucoid MEEs contain harmful factors such as bacterial endotoxins, 2 immune complexes, 3,16 and arachidonic acid metabolites. 17 Those factors can stimulate the production of SOD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that serous and mucoid MEEs contain harmful factors such as bacterial endotoxins, 2 immune complexes, 3,16 and arachidonic acid metabolites. 17 Those factors can stimulate the production of SOD.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have shown that middle ear effusion (MEE) in patients with otitis media with effusion (OME) contains several pathogenic factors such as microorganisms, 1 endotoxins, 2 immune complexes, 3 and arachidonic acid metabolites. 4 Microbial infection is considered to play an important role in the pathogenesis of OME.…”
Section: Introductionmentioning
confidence: 99%
“…In these immunologically naive individuals, natural antibodies may represent an important defense mechanism against influenza virus-mediated pneumococcal disease, as is seen in pneumococcal sepsis (20). Conversely, the formation of immune complexes in the middle ear may facilitate, rather than clear, bacterial OM (21), suggesting that organ-specific differences may exist with regard to the role of antibodies during pneumococcal disease. Moreover, the ability of antibodies to interact with neutrophils in the middle ear (19), and the suggestion that neutrophils may facilitate bacterial OM (14,15), may indicate that the role of antibodies and neutrophils in pneumococcal-influenza virus OM is more complex than simply protecting against disease development.…”
mentioning
confidence: 99%
“…Bacteria, especially Haemophilus influenzae and Streptococcus pneumoniae (normal residents of the nasopharynx), have been cultured from up to 40% of the effusions studied [29,31,[56][57][58]. Under direct microscopy, bacteria are more often visible in mucoid than in serous effusions [59].…”
Section: Bacteriamentioning
confidence: 99%